Rare-earth-doped tellurite distributed Bragg reflector on-chip lasers - Segat Frare, Bruno Luis (My University, 2024)
Tellurite glass is a material with advantageous optical properties, such as high transparency from visible to mid-infrared wavelengths, high nonlinearity, and high solubility of light-emitting rare earth dopants. Although tellurite has been investigated in fibers and in some waveguide studies, there is still much to explore about it in integrated photonics. Here, we use a hybrid platform that monolithically combines tellurite with commercially available silicon nitride chips. The platform leverages silicon nitride’s many advantages, including its low propagation losses, mature fabrication techniques with small feature sizes, and low cost for mass production, to enable the development of new on-chip tellurite glass light sources. This thesis aims to study the optical properties of distributed Bragg reflector cavities and explore their potential for lasing when the tellurite is doped with different rare earths, namely erbium and thulium. Chapter 1 provides an overview of the context of this work, introducing the materials and cavity used here. Chapter 2 introduces the basic theory behind waveguides and Bragg gratings, as well as rare earth rate equation gain models, coupled mode theory, and a laser model based on the shooting method. Chapter 3 discusses the design, fabrication, and characterization of passive properties of distributed Bragg reflector cavities using undoped tellurite. Chapters 4 and 5 present proof-of-concept laser demonstrations, by using tellurite doped with erbium and thulium, respectively. These lasers constitute the first demonstrations of distributed Bragg reflector lasers in this hybrid tellurite-silicon nitride platform. Chapter 6 combines the laser model introduced in Chapter 2 with the designs and results from Chapters 3–5 to investigate different routes to optimize the laser performances by studying how their efficiencies vary with different parameters, such as background loss, cavity and grating lengths, and rare earth concentration. Chapter 7 summarizes this work and provides insights into future research work.
Rare-earth-doped TeO2 distributed Bragg reflector lasers
Keywords: Integrated photonics; tellurite glass; silicon nitride; silicon; rare earth; erbium; thulium; laser; distributed Bragg reflector; Bragg grating; on-chip; tellurium dioxide; sputtering; thin film